Periodontal treatment needs in diabetic and non-diabetic individuals: A case-control study - Manas Das; V Upadhyaya; Srinivas Sulugodu Ramachandra; K D Jithendra (Wolters Kluwer Medknow Publications, 2011)
Aim: Diabetes mellitus is a chronic metabolic disorder of the carbohydrate, protein and fat metabolism, resulting in increased blood glucose levels. Various complications of diabetes have been described with periodontitis being added as the sixth complication of diabetes mellitus. The aim of this study was to assess periodontal status and treatment needs (TN) in diabetic patients and to compare the findings between diabetic and non-diabetic individuals using community periodontal index (CPI). Materials and Methods: We evaluated the periodontal status and periodontal TN in diabetic and non-diabetic individuals in Guwahati, Assam. A total of 459 (223 diabetic and 236 non-diabetic) individuals were assessed. A person was considered to be diabetic when his blood glucose levels were above 140 mg/dl under fasting condition and 200 mg/dl 2 hours postprandially. Periodontal status was assessed using CPI. Results: Periodontal destruction was found to be increased in diabetic individuals, with periodontal destruction increasing with increased blood glucose levels. The necessity of complex periodontal treatment also increased with increasing blood glucose levels. Conclusions: Individuals with diabetes are more prone to periodontal destruction, and hence, regular periodontal screening and treatment is essential in these individuals.